High-resolution near-bottom vector magnetic anomalies over Raven Hydrothermal Field, Endeavour Segment, Juan de Fuca Ridge - Tivey, M A; Johnson, H P; Salmi, M S; Hutnak, M (Journal of Geophysical Research: Solid Earth, 2014)
High-resolution, near-bottom vector magnetic data were collected by remotely operated vehicle Jason over the Raven hydrothermal vent field (47°57.3′N 129°5.75′W) located north of Main Endeavour vent field on the Endeavour segment of the Juan de Fuca Ridge. The survey was part of a comprehensive heat flow study of the Raven site using innovative thermal blanket technology to map the heat flux and crustal fluid pathways around a solitary hydrothermal vent field. Raven hydrothermal activity is presently located along the western axial valley wall, while additional inactive hydrothermal deposits are found to the NW on the upper rift valley wall. Magnetic inversion results show discrete areas of reduced magnetization associated with both active and inactive hydrothermal vent deposits that also show high conductive heat flow. Higher spatial variability in the heat flow patterns compared to the magnetization is consistent with the heat flow reflecting the currently active but ephemeral thermal environment of fluid flow, while crustal magnetization is representative of the static time-averaged effect of hydrothermal alteration. A general NW to SE trend in reduced magnetization across the Raven area correlates closely with the distribution of hydrothermal deposits and heat flux patterns and suggests that the fluid circulation system at depth is likely controlled by local crustal structure and magma chamber geometry. Magnetic gradient tensor components computed from vector magnetic data improve the resolution of the magnetic anomaly source and indicate that the hydrothermally altered zone directly beneath the Raven site is approximately 15 × 106 m3 in volume.
Keywords: ROV Jason (Remotely Operated Vehicle)